AROMA THERAPI DARI KOPI PEMBERANTAS SARANG NYAMUK - Susani Hayati; Nur Muklita Lita; Miki Nuraini; Happy Zalma Fadillah; Linda Andra Pita; Khoiri Zahrotil Hayati (IKATAN ALUMNI DOSEN MAGANG KEMENRISTEKDIKTI TAHUN ANGKATAN 2017, 2024)
Coffee aromatherapy candles are candles that contain fragrant ingredients in the form of coffee which have many benefits and can be used as refreshing, relaxing, curing headaches, eliminating stress and anxiety, improving mood and overcoming insomnia as well as being a solution for the community in efforts to increase the body's immunity. . This article attempts to provide an overview and explanation regarding the work program for making coffee aromatherapy candles, including the process, stages, results and benefits. This article was written using a qualitative approach with a descriptive-explanatory model. As a result, the community receives new understanding and insights regarding the use of agricultural products. This article is limited to the implementation of KKN for the 2023/2024 period